2018
DOI: 10.1097/phm.0000000000000933
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Bedside Respiratory Muscle Training in Patients With Stroke

Abstract: Advanced ACCREDITATION: The Association of Academic Physiatrists is accredited by the Accreditation Council for Continuing Medical Education to provide continuing medical education for physicians.The Association of Academic Physiatrists designates this Journal-based CME activity for a maximum of 1.0 AMA PRA Category 1 Credit(s)™. Physicians should only claim credit commensurate with the extent of their participation in the activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 25 publications
1
36
0
3
Order By: Relevance
“…Of these, 754 were excluded by irrelevancy and 46 were full-text revised. Finally, nineteen studies aimed to assess the effectiveness of RMT on pulmonary function and functional capacity variables in patients with stroke were included in the meta-analysis [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Figure 1 shows the flow of study selection.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 754 were excluded by irrelevancy and 46 were full-text revised. Finally, nineteen studies aimed to assess the effectiveness of RMT on pulmonary function and functional capacity variables in patients with stroke were included in the meta-analysis [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Figure 1 shows the flow of study selection.…”
Section: Resultsmentioning
confidence: 99%
“…The subgroup analysis by type of intervention showed a slightly greater effect in the pooled of the studies that performed only IMT [ES= 0.89 (95% CI: 0.19 to 1.58; I 2 = 66.3%, p = 0.018)] compared with the IMT/EMT subgroup [ES= 0.38 (95% CI: 0.06 to 0.69; I 2 = 0.0%, p = 0.650)]. The FVC was analysed in nine studies [19,23,25,27,29,32,34,36,37]. The pooled ES was 0.32 (95% CI: 0.06 to 0.58; I 2 = 0.0%, p = 0.507) ( Figure 3).…”
Section: Pulmonary Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…38 The finding of significant improvements in pulmonary functions )FVC, FEV1( post-treatment is similar to previous studies. 39 Yoo et al 39 employing a mobility protocol for patients with respiratory failure in ICU showed that both ICU stay and hospital stay were shortened.Sprenkle and Michael 40 found that early mobilization and upright sitting was favorable for patients admitted to neurological ICUs. They stated that mobilization in neurological ICUs could reduce length of stay, hospital acquired infections, and ventilator associated pneumonia.…”
Section: Discussionmentioning
confidence: 99%